Secure resource metering and accounting with hash chain in cloud storage - Mei LIU; Ge FU; Yi-xi LI; Hong ZHANG; Xin-ran LIU; Cui-lan DU (Tongxin xuebao)
Cloud storage is a pay-per-use service of which the billing plan is typically based on users' resource consump-tion metered by server side. Therefore, the trustworthiness between payer and service provider becomes a key factor for the business, and triggers security concerns. On the one hand, service providers or insiders may inflate the amount of re-source consumed to get more service charge. On the other hand, payers may deny the resource consumption to pay less. Thus, a resource metering and accounting scheme based on hash chain was proposed. It generated verifiable proof for different types of resources. For most resources, proof can be generated based on total amount of resource incurred. How-ever, similar scheme cannot be applied to storage space usage, since it fluctuates and the billing relies on not only the utilized storage space but also the storage duration. The proposed storage usage metering scheme considers time factor together with storage space, and generates proof according to the diverse storage billing plans. It improves previous schemes, and achieves the goal of verifiable metering and accounting.